Determination of some hematological and biochemical changes in male rats exposed to drug gemzar and the role the aqueous extract of stigma plant saffron in relieving it - khudhair Al-mayali, Hussein; Hassan Ibrahim, Iraq (Al-Qadisiyah Journal of Pure Science, 2018)
The current study is designed to determine the biochemical effects and hematological-effect induced drug Gemzar that as well as to recognize the role played by the aqueous extract of stigma plant saffron in reducing the toxicity of the drug chemotherapy (gemzar) resulting from it, as it was used in this experiment (60) adult white rats aged between (9-12) a week, and were divided into five groups (twelve animals per group) the first negative control group gavage by Normal saline and ad allium , the second group of control positive been gavage drug (Gemzar) at a dose of 15 mg / kg only of body weight and third gavage aqueous extract at a dose of (100) mg / kg of body weight before than drug for two weeks. The fourth was gavage aqueous extract with the drug together at the same time. Fifth Group gavage aqueous extract after the drug two weeks. Continued duration of the experiment (four weeks) and then were sacrificed animals and draw blood, including for the purpose of shows pathological effects occurring in the studied parameters, where the results of statistical analysis showed a significant decrease in weight total body and high moral in liver weight for a property compared with the control group. the results also showed for significant increase in the level of liver enzymes (ALT, AST, ALP) for a positive control. the results also showed that there were significant differences in the level of total cholesterol-triglyceride range of positive control . the results showed a significant decrease in the hematological standards and represented a rate (RBC, WBC, Hb, PVC). showed a microscopic examination of the liver of the rat results of treatment with a drug gemzar concentration of 15 mg / kg for a period of four weeks (positive control) compared with negative control demonstrated by the occurrence of tissues changes clearly represented the occurrence of severe congestion (congestion) with a clear expansion in sinusoids liver, and the presence of inflammatory cells, particularly of the type of cells macrophage. But when the interfene between the plant extract concentration of 100 mg / kg of body weight and drug in three transactions a treatment aqueous extract (before with, after) the drug study showed a clear improvement and soon in some cases from the totals for the negative control. It can be concluded that exposure to the drug led to changes tissues satisfactory and clear the liver as well as for changes in the biochemical parameters and hematological blood rats -treatment drug, and proved the current study, that give the plant extract together simultaneously with the property and sometimes (before and after) the drug has the active role to reduce the damage and toxic effects caused by the drug.